Sociodemographic and clinical risk markers for operant behavior in patients with different types of chronic pain - Asanova, Azize (Psychosomatic Medicine and General Practice, 2025)
Background. Chronic pain is a complex medical and social problem that significantly reduces patients’ quality of life, work capacity, and level of social integration. It develops not only through biological mechanisms but also under the influence of psychosocial factors, including behavioral and socio-demographic determinants. Evidence shows that persistent pain syndromes are strongly associated with an increased risk of affective disorders, operant (pain-related) behavior, and opioid analgesic dependence. A proactive psychological and psychiatric approach to identifying high-risk groups is critical for developing personalized therapeutic strategies. Objective. To determine the role of socio-demographic factors (age, sex, education, marital and financial status, place of residence) and clinical markers (type, intensity, duration of pain, psycho-emotional state) in the development of operant behavior in patients with chronic pain syndromes and disorders, and to assess the predictive value of the DIRE scale for early risk stratification. Methods. The study included 302 patients aged 18–70 years with various forms of chronic pain (primary, secondary and mixed) lasting more than three months. Patients were stratified into five groups according to ICD-11 and clinical-psychopathological criteria: primary-psychogenic pain, psychophysiological pain, mixed primary-psychogenic and psychophysiological pain, secondary organic pain, and secondary mixed pain. Socio-demographic characteristics and clinical parameters were analyzed in relation to the DIRE scale scores. Results. The highest risk of operant behavior was observed in the PPP3 group (mixed primary-psychogenic and psychophysiological pain), where 84–90% of patients had a total DIRE score <14, indicating high behavioral vulnerability. In the SOP group (secondary organic pain), a negative correlation between pain intensity and risk was found (Rho = –0.42; p < 0.01), indicating a stable pain perception profile and low likelihood of operant behavior and opioid dependence. Socio-demographic factors (marital status, education, financial situation, place of residence) did not show an independent statistically significant effect on risk. However, younger age was identified as a key predictor of increased vulnerability in the PPP1 (primary-psychogenic), PPP2 (psychophysiological), PPP3 (primary mixed), and SMP (secondary mixed) groups. Pain intensity was behaviorally relevant only in psychogenic and mixed pain syndromes. Conclusions. Socio-demographic characteristics alone do not determine the risk of operant behavior but modulate it in interaction with clinical and psycho-emotional factors. Younger age and psychogenic pain are the most significant predictors of high risk. The DIRE scale is an effective tool for risk stratification and supporting personalized clinical decision-making: opioid therapy may be more appropriate for low-risk groups (SOP), whereas multimodal psychotherapeutic and behavioral interventions should be prioritized for high-risk groups (PPP3). Keywords: chronic pain; operant behavior; pain behavior; socio-demographic factors; clinical predictors; DIRE; opioid therapy.